Men and Citizens in the Theory of International Relations - Linklater, Andrew (London, 1982)
This book began as a doctoral thesis submitted to the University of London in 1978. In the course of writing my thesis, and subsequently redrafting it for publication, Author has incurred many obligations. Firstly, author would like to record his gratitude to the Trustees of the Noel Buxton Studentship in International Relations at the London School of Economics for provision of financial support between 1974 and 1976. While a student in the Department of International Relations Author had the privilege of being supervised by Michael Donelan whose encouragement, advice and example were invaluable.
Keywords: International Relations